1973
DOI: 10.1017/s0014479700023693
|View full text |Cite
|
Sign up to set email alerts
|

Size and Shape of Plots for Estimating Yield Losses from Cereal Foliage Diseases

Abstract: Data from uniformity trials on healthy and diseased wheat and oat crops showed that the coefficient of variation for yield decreased as plot size increased and became nearer to square in shape. Infection with Septoria leaf blotch of oats and powdery mildew of wheat did not appear to affect yield variability. Plots larger than rod row size (where 16 ft of the centre row of 3 rows is harvested) are recommended to detect differences of 1 o per cent in yield between two treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…The immediate consequence of this lack of mobility is the fact that the shape of the plot or field in which the plants are distributed may significantly affect disease dynamics. In fact, there is both empirical and theoretical evidence that supports this hypothesis [22][23][24][25][26][27][28][29][30]. In general, it has been suggested that square plots and fields favored higher spreading of plant diseases than elongated ones of the same area [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The immediate consequence of this lack of mobility is the fact that the shape of the plot or field in which the plants are distributed may significantly affect disease dynamics. In fact, there is both empirical and theoretical evidence that supports this hypothesis [22][23][24][25][26][27][28][29][30]. In general, it has been suggested that square plots and fields favored higher spreading of plant diseases than elongated ones of the same area [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In those cases, the size and shape of the plots is controlled typically to estimate crop yields. Thus, they are typically of almost perfect square or rectangular shapes (see for instance [24]). The second scenario is when crops are cultivated in country fields.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If this is not possible, (16)(17)(18)(19)(20)(21)(22) has made especially important contributions to the science of crop loss assessment. In an elegant and pioneering series of papers in the 1970s, James and co-workers (16)(17)(18)(19)(20)(21)(22) showed that crop loss assessment and modeling are, indeed, of scientific merit. Methods for measuring and quantifying disease intensity in single plants and fields (23,24,42) and for determining and predicting crop losses are improving.…”
Section: Canonical Correlation Determines the Association Between Thementioning
confidence: 99%
“…Preliminary (16). First, the experiments should be conducted in more than one experiments should be conducted to determine sample sizes needed location, and preferably in areas where the crop is normally grown to produce results with a certain level of precision (19). Often there and the disease is important.…”
mentioning
confidence: 99%